Formulation and Evaluation of Transdermal Dissolving Microneedle Loaded with Ethanol Extract of Cocor Bebek Leaves (Kalanchoe pinnata) - Balapadang, Rachel Noveriachristie; Sarie, Aldila Divana; Rosyidah, Safira; Zulqifli, Iqbal; Akifah, Muthia Nur; Zahra, Aliya Azkia (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Acne is a chronic skin inflammation caused by blockage of the sebaceous glands in the skin and hypercolonization of the acne-causing bacteria Propionibacterium acnes. Cocor bebek leaves (Kalanchoe pinnata) are known to contain various secondary metabolites, including flavonoids, with antibacterial activity. Objective: In an effort to prevent side effects from using oral and topical antibiotics to treat acne, an alternative acne treatment that is safer and more effective with a strong drug delivery system is needed: microneedle patch technology containing natural ingredients. Methods: A microneedle patch formulation of Cocor bebek leaf extract was developed using a combination of HPMC and PVP polymers. The evaluation of microneedle patches included irritation tests with rat test animals and antibacterial activity tests against Propionibacterium acnes. The results showed the formation of yellow microneedle patches with uniform needles. The evaluation results showed that the microneedle patch has an irritation index value classified as non-irritant and has antibacterial activity against Propionibacterium acnes, with the highest inhibitory diameter at an extract concentration of 30% with a moderate inhibition category. Conclusion: The microneedle patch cocor bebek leaf extract shows potential as an effective drug delivery system for the treatment of acne that is safe for use on the skin.